A Comparative Taxonomic Study of the Chemo-Physiological and Anatomical Traits of Ten Date Palm (Phoenix dactylifera L.) Cultivars Propagated via Tissue Culture and Vegetative Methods - Salim, Al-hamza A.; Suhaim, Aqeel A.; Jaffer, Osama N (Basrah Journal Of Date Palm Research, 2025)
Date palm (Phoenix dactylifera L.) is considered one of the most economically important trees due to its nutritional and cultural significance in various communities. Given the diversity of date palm cultivars and propagation methods, the need for scientific classification keys has increased to facilitate cultivar differentiation. This study aimed to investigate certain chemo-physiological and anatomical traits of ten date palm cultivars—five propagated via tissue culture (Barhi, Sukkary, Khalas, Zamli, and Maghrabi) and five propagated vegetatively (Barhi, Hassawi, Braim, Deiri, and Shukr)—to evaluate the biochemical content of their leaves, including plant pigments (chlorophylls and carotenoids), carbohydrates, and amino acids, in addition to anatomical characteristics. The results revealed considerable variation among the cultivars in most of the traits studied, which can be considered distinctive and potentially used as taxonomic markers for cultivar identification